2008
DOI: 10.1159/000118759
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of the fragile histidine triad <i>(FHIT)</i> tumor suppressor gene in vesical tumors of cattle with chronic enzootic hematuria (CEH)

Abstract: The FHIT (fragile histidine triad) gene is a tumor suppressor gene known to be inactivated in many tumors including bladder tumors and is spanning FRA3B, a very active common fragile site in the human genome. We have recently isolated the bovine gene, and the aim of this study was to test whether FHIT presents altered expression patterns in vesical tumors of cattle with CEH (chronic enzootic hematuria). CEH is a common syndrome affecting Mediterranean cattle: clastogenic, mutagenic and cancerogenic substances … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 24 publications
3
5
0
Order By: Relevance
“…Figure 4A shows the 5' FHIT transcript organisation in the horse genome. The equine FHIT 5'UTR region organization is comparable with the data deriving from other species such as Bos [17]. The DNA sequences of both transcripts have been deposited in GenBank [JN403048, JN403049].…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…Figure 4A shows the 5' FHIT transcript organisation in the horse genome. The equine FHIT 5'UTR region organization is comparable with the data deriving from other species such as Bos [17]. The DNA sequences of both transcripts have been deposited in GenBank [JN403048, JN403049].…”
Section: Resultssupporting
confidence: 53%
“…In a variable percentage of cases, depending on the tumour type, FHIT loss of function is determined by the hypermethylation status of the associated CpG island with the consequent repression of gene transcription [11]. While alterations in the FHIT gene have been reported in several human cancers, the putative role of this tumour suppressor gene and its epigenetic alteration in animal tumours are not well known [17,18]. In order to obtain new insights into BPV-mediated carcinogenesis, we investigated the status of FHIT protein expression in equine sarcoid cell lines and sarcoid tumours.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the number of viral DNA copies has been shown to be significantly higher in more aggressive sarcoids, compared with their slowgrowing counterparts [33]. Over the years, the expression of several cancer markers has been studied in equine sarcoids, such as the tumour suppressor gene fragile histidine triad (FHIT), which was found to be down-regulated [34] as in human cervical cancer [35] although, curiously, not in BPV-associated bovine urinary tumours [36]. Such differences make spontaneous, BPV-induced, animal cancer models particularly useful to study the influence of specific host's genes in the carcinogenic process.…”
Section: Bpv-induced Cell Transformationmentioning
confidence: 99%
“…On the other hand, it was suggested that the promoter gene methylation of FHIT is one of the reasons for inactivation mechanisms of suppressor activity (Stam et al 2006;Guidi et al 2008).…”
Section: Tumor Suppressionmentioning
confidence: 99%